Salmon P. Chase : a biography - Niven, John (Oxford University Press, 1995)
A biography of Salmon P. Chase, one of the principal political figures in the American Civil War period. A rival to Abraham Lincoln for the Republican Presidential nomination in 1860, he subsequently became Secretary of the Treasury in Lincoln's war-time cabinet.
Keywords: Chase, Salmon P. -- (Salmon Portland), -- 1808-1873.; United States. -- Congress. -- Senate -- Biography.; États-Unis. -- Congress. -- Senate -- Biographies.; Chase, Salmon P. -- (Salmon Portland), -- 1808-1873; United States. -- Congress. -- Senate; Legislators -- United States -- Biography.; Judges -- United States -- Biography.; Governors -- Ohio -- Biography.; United States -- Politics and government -- 1849-1877.; Parlementaires -- États-Unis -- Biographies.; Juges -- États-Unis -- Biographies.; Gouverneurs -- Ohio -- Biographies.; États-Unis -- Politique et gouvernement -- 1849-1877.; HISTORY -- State & Local.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical.; HISTORY -- State & Local -- General.; Governors; Judges; Legislators; Politics and government; Ohio; United States; 1849-1877; Politics -- History, 1845-1901; Biographies; Biographies.